Optimizing Public Health Services through the Implementation of IoT Sterilization and Water Purifier Technology at the Kemuning 1A Integrated Health Post in Sukamakmur Village, Ciomas, West Java: Optimalisasi Layanan Kesehatan Masyarakat melalui Implementasi Teknologi IoT Sterilization dan Water Purifier di Posyandu Kemuning 1A Desa Sukamakmur, Ciomas, Jawa Barat - Nyayu Siti Aminah Lily Elfrieda; Sata Yoshida Srie Rahayu; Johan Iskandar; Yuli Wahyuni (Universitas Lancang Kuning, 2025)
The people of Sukamakmur Village, Ciomas, West Java, face limited access to health care and clean water. This problem has resulted in a decreased quality of life, increased risk of water-based diseases, and low public understanding of clean and healthy lifestyles. This community service program attempts to provide solutions through the implementation of IoT Sterilization and Water Purifier technology at the Kemuning 1A Integrated Health Post (Posyandu). The goal is to improve Posyandu health services, ensure the availability of clean drinking water, and empower Posyandu cadres to be independent in the use and maintenance of technology. This is in line with SDG 3 (Healthy and Prosperous Life) and SDG 6 (Clean Water and Adequate Sanitation) through training and mentoring activities on the use of IoT Sterilization and Water Purifier devices, as well as socialization and counseling on healthy lifestyles and the importance of clean drinking water to support the realization of a healthy and prosperous life. The activity methods include socialization, cadre training, mentoring on the use of tools, technology application, and program evaluation and replication. In terms of increasing community knowledge through the transfer of IoT Sterilization technology to sterilize and kill microbes, positive behavioral changes in water use and management, the community's ability to operate and maintain equipment independently, and cadres acting as health education facilitators, the empowerment of partners in the social aspect of the community has increased from 20% to 80%. Meanwhile, in terms of improving management capabilities, this is reflected in the availability of clean water access directly at the Integrated Health Post (Posyandu), the development of documentation and program models that can be adapted by other Posyandus, resulting in an increase in partner empowerment in the management aspect from 35% to 85%.